THE PRIORITY OF VALUE-SEMANTIC ORIENTATIONS IN HIGHLY QUALIFIED ATHLETES - Liashenko, Valentina; Omelchenko, Tatyana; Gatsko, Elena; Gnutova, Natalya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
A stable structure of life values is one of the components of success in sports. When defining the value of value as a category of psychology, based on data from many authors, we denote that it reveals value as a concept used in philosophy and sociology to designate objects and phenomena that are significant in the life of society, social groups and individuals. Athletes who have achieved high results are dominated by such life values as “spiritual satisfaction” (74%) and “achievements” (61%). Since “spiritual satisfaction” is a moral value, it becomes obvious that it is moral values that motivate athletes to achieve high results. According to the results of multiple regression of terminal values in the total sample of athletes (n = 118, p <0.05), we observe that the “achievement” of qualified athletes is most affected by “spiritual satisfaction”. In second place in terms of contribution to the formation of “achievement” value is “own prestige”, and in third place is “financial standing”. The value hierarchy of athletes also contains such a value as “self-development”, which indicates the athlete’s desire to work on himself, his character, the development of necessary abilities and other subjectively important characteristics of his personality.